The People's Bank of China's response to the coronavirus pandemic: A quantitative assessment - Michael Funke; Andrew Tsang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
The People's Bank of China (PBoC) has taken numerous measures to cushion the impacts of the COVID-19 health crisis on the Chinese economy. As the current monetary policy framework features a multi-instrument mix of liquidity tools and pricing signals, we employ a dynamic-factor modeling approach to derive an indicator of China's monetary policy stance. Our approach assumes that comovements of several monetary policy instruments share a common element that can be captured by an underlying unobserved component. We use the derived indicator to trace the response of the PBoC to the coronavirus pandemic. The estimates reveal that the PBoC has implement novel policy measures to ensure that commercial banks maintain liquidity access and credit provision during the COVID-19 crisis.
URN:NBN:fi:bof-202006022166
Keywords: C54; E32; E52; I15; 330; corona pandemic; COVID-19; China; monetary policy; dynamic factor model